2005
DOI: 10.1515/bc.2005.054
|View full text |Cite
|
Sign up to set email alerts
|

Adrenodoxin (Adx) and CYP11A1 (P450scc) induce apoptosis by the generation of reactive oxygen species in mitochondria

Abstract: Mitochondrial cytochrome P450 systems are an indispensable component of mammalian steroid biosynthesis; they catalyze regio- and stereo-specific steroid hydroxylations and consist of three protein entities: adrenodoxin reductase (AdR), adrenodoxin (Adx), and a mitochondrial cytochrome P450 enzyme, e.g., CYP11A1 (P450 side chain cleavage, P450scc). It is known that the latter two are able to generate reactive oxygen species (ROS) in vitro . In this study, we investigated whether this ROS generation also occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…Reactive oxygen species are normal byproducts of steroidogenesis due to electron leakage from the mitochondrial electron transport chain (17,18). Moderate amounts of ROS are compensated, for example, by catalase activity and the glutathione cycle, and, interestingly, are considered to be physiologically key molecules in oocyte maturation and fertilization.…”
mentioning
confidence: 99%
“…Reactive oxygen species are normal byproducts of steroidogenesis due to electron leakage from the mitochondrial electron transport chain (17,18). Moderate amounts of ROS are compensated, for example, by catalase activity and the glutathione cycle, and, interestingly, are considered to be physiologically key molecules in oocyte maturation and fertilization.…”
mentioning
confidence: 99%
“…Although the increase in mitochondrial ROS production after expression of Adx 1-108 in strain CAD48 was more than threefold in comparison to the background level, it did not cause cell death. For comparison, after transient expression of human Adx-WT in cell line HCT116 p53 -/-ROS formation increased merely by a factor of 1.6 (as measured by the same detection assay) but caused a drop in cell survival by more than 50% [20]. To the best of our knowledge, these findings provide the first example of strong ROS production being not linked to cell death in fission yeast.…”
Section: Resultsmentioning
confidence: 68%
“…We recently reported that transient overexpression of human or bovine Adx is sufficient to cause significant ROS formation in the mitochondria of mammalian cells, with an increase in mitochondrial ROS formation of about 60% above basal levels being sufficient to strongly induce apoptosis [20]. The aim of this study was to investigate the effects of Adx expression in the fission yeast S. pombe and to compare it to Adx-induced cell death in mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the autoxidation shunt accounts for a major fraction of reactive oxygen species (ROS) in mammalian P450 CYP11A1, both in vivo and in vitro 12 and this can lead to the induction of apoptosis in cells.…”
Section: Introductionmentioning
confidence: 99%